Eficiência na tributação do Imposto sobre a Propriedade Predial e Territorial Urbana (IPTU): uma análise para o Município de Fortaleza – Ceará - Firmeza, Renato de Miranda (2024)
This dissertation investigates the efficiency of Urban Property Tax (IPTU) collection in Fortaleza city over the period from 2013 to 2022. Employing Data Envelopment Analysis (DEA) methodology on a panel dataset, encompassing municipalities in the state of Ceará as decision units, the study assesses the relative efficiency of different municipal administrations in IPTU collection. The findings reveal a decline in Fortaleza's relative efficiency in IPTU taxation, decreasing from 75% during the initial period (2013-2018) to 56% in the last period (2017-2022). Moreover, the research conducts a detailed examination of revenue loss stemming from IPTU registrations lacking valid taxpayers and inaccuracies in taxpayer registration, thereby identifying deficiencies in collection effectiveness. The outcomes of this study contribute valuable insights into efficient practices in municipal tax management, offering essential guidance for enhancing tax policies and addressing the root causes of municipal revenue loss.